2006
DOI: 10.1086/497973
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Decomposition of Broad-Line AGNs and Host Galaxies

Abstract: Using an eigenspectrum decomposition technique, we separate the host galaxy from the broad line active galactic nucleus (AGN) in a set of 4666 spectra from the Sloan Digital Sky Survey (SDSS), from redshifts near zero up to about 0.75. The decomposition technique uses separate sets of galaxy and quasar eigenspectra to efficiently and reliably separate the AGN and host spectroscopic components. The technique accurately reproduces the host galaxy spectrum, its contributing fraction, and its classification. We sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
139
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 84 publications
8
139
1
Order By: Relevance
“…All of these predictions appear to be opposite the observations, with quasar spectra dominated by poststarburst activity (Vanden Berk et al 2006), typically early-type, bulge-dominated hosts (especially in the brightest quasars; Dunlop et al 2003;Floyd et al 2004), and observed starbursts usually showing high accretion rate BHs, which are at that moment undermassive relative to their hosts (e.g., Borys et al 2005). Moreover, if star formation is ongoing in these objects to grow their bulges, it implies a lower mass-to-light ratio and suggests that the discrepancy between their M BH -host relations is even larger than that in Figure 2, amplifying these difficulties.…”
Section: Discussionmentioning
confidence: 60%
“…All of these predictions appear to be opposite the observations, with quasar spectra dominated by poststarburst activity (Vanden Berk et al 2006), typically early-type, bulge-dominated hosts (especially in the brightest quasars; Dunlop et al 2003;Floyd et al 2004), and observed starbursts usually showing high accretion rate BHs, which are at that moment undermassive relative to their hosts (e.g., Borys et al 2005). Moreover, if star formation is ongoing in these objects to grow their bulges, it implies a lower mass-to-light ratio and suggests that the discrepancy between their M BH -host relations is even larger than that in Figure 2, amplifying these difficulties.…”
Section: Discussionmentioning
confidence: 60%
“…Lacking the data to measure the host galaxies of our sources, we must estimate their contribution. Such estimates of the contribution of host galaxy light to the SEDs can be made by applying simple scaling relationships among host bulge luminosity, bulge mass, black hole mass, and Eddington luminosity (e.g., Dunlop et al 2003;Vanden Berk et al 2006). The well-known correlation between central black hole mass and both bulge mass and luminosity (e.g., Ferrarese 2002) implies that quasars accreting at near their Eddington limits must have host bulge masses, and therefore luminosities, large enough to harbor the inferred black hole.…”
Section: Mean Sedsmentioning
confidence: 99%
“…The well-known correlation between central black hole mass and both bulge mass and luminosity (e.g., Ferrarese 2002) implies that quasars accreting at near their Eddington limits must have host bulge masses, and therefore luminosities, large enough to harbor the inferred black hole. We have used the quasar luminosity versus host luminosity relationship at optical frequencies, described by Vanden Berk et al (2006), to estimate the relative host galaxy contribution, assuming that the quasars are emitting at their Eddington limits.…”
Section: Mean Sedsmentioning
confidence: 99%
“…Studies of stellar populations through broadband SEDs and optical spectra have discovered intermediate-age stars or bluer colors in AGN hosts compared to their inactive galaxy counterparts at both low redshift (Ronnback et al 1996;Brotherton et al 1999;Kauffmann et al 2003a;Jahnke & Wisotzki 2003;Jahnke et al 2004;Canalizo et al 2006;Vanden Berk et al 2006;Jahnke et al 2007;Schawinski et al 2009) and high redshift (Ammons et al 2009). In the following, we show that the spectral features employed by current studies of stellar populations are not sensitive to ongoing (<0.1 Gyr) starburst activity.…”
Section: Comparisons With the Study Of Stellar Populationsmentioning
confidence: 99%
“…More importantly, obscuration can hide blue host-galaxy light if star formation occurs in the circumnuclear region as discussed above. Therefore, results based on spectra extending shorter than < 4000 Å may still underestimate significantly the level of ongoing star formation activity (Jahnke et al 2007;Vanden Berk et al 2006;Chen et al 2009). Kauffmann et al (2003a) employed the 4000 Å break and Hδ absorption to study stellar populations and found intermediateage stars in hosts with early-type morphologies.…”
Section: Comparisons With the Study Of Stellar Populationsmentioning
confidence: 99%